KAJIAN PERENCANAAN BISNIS PADA USAHA KECIL DAN MENENGAH (STUDI PADA USAHA PERCETAKAN TELA PRES, KERAJINAN BESI PUTIH, DAN PENGRAJIN OVEN DI DARUBA KABUPATEN PULAU MOROTAI) - Sabuhari, Rahmat (Jurnal Manajemen Sinergi, 2014)
Abstract Micro, Small and Medium Enterprises (SMEs) is a business that is managed by the community that continues to grow and evolve in tune with the growth of the nation's economy. This study aims to determine the model of business planning, implementation planning, and problems that hinder business stats faced by the MSMEs in the District of Morotai Island. The method used in this research is qualitative research, interviewing some of the informants as respondents. The results showed that the white metal craftsman and kitchen tools lack an understanding of business planning so that business is less developed, businessmen will tela pres deeply understand business planning to sustain their business, not their long-term business objectives, the employee also can not implement the plan with the business rancana well, on the other hand employees can complement each other's work, if an employee is absent. The things that cause against less concerned for entrepreneurs to business planning is always ignored. Finally expected on craftsmen or business owners to be able to make a formal planning, because it can be useful in the coming period, as well as a description of the work to employees or members of the craftsmen will work dikerajakannya, and the District Government Morotai Island, presumably can help the SME my head in terms of the management training and business planning for entrepreneurs to have skills in business planning.